The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/bf02574515
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of lymph node tumor burden in melanoma patients staged by sentinel node biopsy

Abstract: Microstaging of melanoma sentinel lymph node/CLND specimens by using the diameter of the largest tumor deposit is a highly significant predictor of early relapse and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 12 publications
3
45
0
1
Order By: Relevance
“…The rates for positive CLNDs were not significantly different for SLN macrometastases and micrometastases. This is in accordance with other studies in which reproducible prediction of non-SLN positivity on the basis of SLN tumour burden remained elusive (Ranieri et al, 2002;Carlson et al, 2003;Pearlman et al, 2006;Roka et al, 2008). Additional positive non-SLNs upon CLND are widely recognised to adversely influence prognosis (Carlson et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The rates for positive CLNDs were not significantly different for SLN macrometastases and micrometastases. This is in accordance with other studies in which reproducible prediction of non-SLN positivity on the basis of SLN tumour burden remained elusive (Ranieri et al, 2002;Carlson et al, 2003;Pearlman et al, 2006;Roka et al, 2008). Additional positive non-SLNs upon CLND are widely recognised to adversely influence prognosis (Carlson et al, 2003).…”
Section: Discussionsupporting
confidence: 90%
“…Roka et al (2008) were able to partly confirm this: even though no significant association between SLN tumour load and non-SLN positivity was found, the rate of DFS for patients with an SLN tumour burden of 42 mm was significantly worse. Similar observations come from a study by Ranieri et al (2002), albeit with a cutoff at 3 mm. Our own data confirm these results in part: SLN tumour burden with a cutoff at 2 mm was indeed a significant prognosticator for tumour recurrence (P ¼ 0.005, log-rank test), with the rates of relapse during the median observation period more than twice as frequent for SLN macrometastases (51.3%) as for micrometastases (24.6%).…”
Section: Discussionsupporting
confidence: 84%
“…11,29 The approach of using micrometric assessment of metastatic tumor diameter has been profitably developed by Starz et al, 30,31 in Augsburg, and alone or in combination with determination of the number of 1-mm-thick slices of the sentinel nodes that contain tumor applied to the evaluation of sentinel nodes. The use of ocular micrometers to evaluate the diameter of metastases in sentinel node has also been reported by Wagner et al, 32 and Ranieri et al 33 We are currently collaborating with the Augsburg group to compare the predictive value of area measurements of nodal tumor with the information obtainable by evaluation of the micrometer-measured maximum diameter nodal tumor. If the micrometer approach provides guidance comparable to the tumor predictive accuracy of tumor area assessment, it would be preferable as a relatively simple approach since the technique is already widely used in routine anatomic pathology evaluation.…”
Section: Discussionmentioning
confidence: 62%
“…In comparison with the high literature coverage of NSLN involvement predictive factors, few data are reported on this latter topic. Previous studies indicated that the dimensions of nodal tumour deposits could be significant predictors [37] and [38]. Roka et al [8] reported an SLN tumour size >2 mm, presence of NSLN involvement and Breslow thickness to be associated with different recurrence-free and disease-specific survival and confirmed the prognostic relevance of the S/U score proposed by Reeves et al [20] In another paper, the presence of micro-metastatic tumour deposits in SLN was associated to a significantly better prognosis with respect to macrometastases [9].…”
Section: Discussionmentioning
confidence: 99%